Need Response Analysis to the Development of E-Comics in Material Quantities and Units - Septiana, Eliza; Risdianto, Eko; Hamdani, Dedy; Abdu, Muhammad; Endang, Endang (Graduate Program Magister Manajemen Pendidikan, 2022)
This research aims to analyze the response to the needs of E-Comic-based learning media for high school students. Data analysis techniques are carried out using quantitative data analysis and concluded with qualitative analysis. This study is an R n D study with the ADDIE model. In this study the stage used is the stage of needs analysis, the instrument used in this study is a school observation sheet, interview sheet, and a need questionnaire sheet for E-Comic-based learning media. Data collection techniques are using observation data, interviews, and questionnaire data. The subjects used in this study were physics teachers and X-class learners at SMA N 6 and SMA N 8 Bengkulu City with a total of 169 students and 5 teachers. The results of this study showed that the instrument used was valid and reliable. The results of this study also showed that high school students and teachers strongly agree and needed E-Comic-based learning media. The results of this study showed that the instrument used was valid and reliable. Therefore, from these results, researchers hope to contribute to education practitioners in order to develop teaching materials in the form of E-Comic Materials and Units for students.